Characterization of myelin oligodendrocyte glycoprotein (MOG)(35–55)-specific CD8(+) T cells in experimental autoimmune encephalomyelitis - Peng, Yong (Chin Med J (Engl), 2019)
BACKGROUND: The pathogenesis of multiple sclerosis (MS) is mediated primarily by T cells, but most studies of MS and its animal model, experimental autoimmune encephalomyelitis (EAE), have focused on CD4(+) T cells. The aims of the current study were to determine the pathological interrelationship between CD4 and CD8 autoreactive T cells in MS/EAE. METHODS: Female C57BL/6 mice (n = 20) were induced by myelin oligodendrocyte glycoprotein (MOG)(35–55) peptide. At 14 days after immunization, T cells were isolated from the spleen and purified as CD4(+) and CD8(+) T cells by using CD4 and CD8 isolation kits, and then the purity was determined by flow cytometric analysis. These cells were stimulated by MOG(35–55) peptide and applied to proliferation assays. The interferon-gamma (IFN-γ) and interleukin (IL)-4 secretion of supernatant of cultured CD4(+) and CD8(+) T cells were measured by enzyme-linked immunosorbent assays (ELISA). For adoptive transfer, recipient mice were injected with MOG(35–55)-specific CD8(+) or CD4(+) T cells. EAE clinical course was measured by EAE score at 0–5 scale and spinal cord was examined by staining with hematoxylin and eosin and Luxol fast blue staining. RESULTS: CD8(+)CD3(+) and CD4(+)CD3(+) cells were 86% and 94% pure of total CD3(+) cells after CD8/CD4 bead enrichment, respectively. These cells were stimulated by MOG(35–55) peptide and applied to proliferation assays. Although the CD8(+) T cells had a generally lower response to MOG(35–55) than CD4(+) T cells, the response of CD8(+) T cells was not always dependent on CD4. CD8(+) T cell secreted less IFN-γ and IL-4 compared with CD4(+) T cells. EAE was induced in wildtype B6 naïve mice by adoptive transfer of MOG(35–55)-specific T cells from B6 active-induced EAE (aEAE) mice. A similar EAE score and slight inflammation and demyelination were found in naive B6 mice after transferring of CD8(+) T cells from immunized B6 mice compared with transfer of CD4(+) T cells. CONCLUSION: Our data suggest that CD8(+) autoreactive T cells in EAE have a lower encephalitogenic function but are unique and independent on pathogenic of EAE rather than their CD4(+) counterparts.